Energy-Performance Concrete Roof Slabs in Hot Climates Using Air Ventilation and False Ceiling with Baffles Shape: A Numerical and Modeling Study - Hersh F. Mahmood; Hiwa Abdlla Maarof; Masood Abu-Bakr; Amira Soud (Journal of Studies in Science and Engineering, 2022)
The thermal performance of a concrete roof between the main slab (concrete slab) and secondary slab (gypsum board) has been investigated in this work with and without a ventilator. The hourly averaged climatic data (combined optical and thermal condition) of the external roof surface was used as the resource for the boundary conditions of Erbil city (Kurdistan Region, Iraq). The results of measuring the effects of using a ventilator between the concrete slabs and gypsum boards indicated that the moving air in the layer between slabs by using the ventilation process has more effect in cooling roofs and the room temperature had less than that of slabs that do not use ventilation, and so using baffle shape gypsum board as the secondary slabs for air turbulence to increase air velocity, the number of mass flow rates have more efficient in the cooling process and fast the cooling process, the surface temperature was reduced by (4.5oC and 3.6 oC) with the mass flow rates of (3.5kg/s)  and (2kg/s) respectively,  this is due to moving air makes roof slab cool and loss the heat that transfers through the slabs, so using this technique for an exciting roof is a good choice